N-acetyl-L-cysteine and lauric acid; effective antioxidant and antimicrobial feed additives for juvenile Pacific white shrimp (Litopenaeus vannamei) cultured at high stocking density - Shafaq Fatima (PLoS ONE, 2025)
Present study aimed at improving the immune and antioxidant response of Pacific white shrimp (Litopenaeus vannamei) cultured at high stocking density fed with 0.2% supplementation of lauric acid (LA) and N-acetyl-L-cysteine (NAC). Shrimp (initial average weight = 0.65 g; n = 270) were grown at low stocking density (LSD) (n = 10/0.80 ft3 per replicate) and high stocking density (HSD) (n = 20/0.80 ft3 per replicate). They were randomly distributed into five groups (T1: negative control at LSD, T2: positive control at HSD, T3: at HSD and fed with LA supplement diet, T4: at HSD and fed with NAC supplemented diet, T5: at HSD and fed with combination of LA and NAC). All these five treatments were studied in triplicates and study continued for eight weeks. Better growth and higher levels of glucose, total protein, total hemocyte count and phagocytic index were observed in shrimp fed with NAC and LA supplemented diets. Observed survival rate and feed conversion ratio in all treatments was 75–89% and < 0.82, respectively. All parameters indicating stress were observed to be higher in T1 as compared to T2. Improved expression of superoxide dismutase and glutathione peroxidase and lower levels of malondialdehyde genes in T3, T4 and T5 showed that supplementation with these nutraceuticals can improve antioxidant response at high stocking density. A parallel increase was observed in the profiles of prophenoloxidase and lysozyme, underscoring the immune-boosting effects of both NAC and LA. This finding was further supported by higher expression of innate immune signaling pathway-related gene, toll like receptor-2 in T3, T4 and T5. In conclusion, NAC and LA, can possibly improve the resistance of white pacific shrimp against oxidative stress and pathogens when cultured in intensive production system.